Characterization of core clinical phenotypes associated with recurrent proximal 15q25.2 microdeletions. Issue 1 (21st November 2013) - Burgess, Trent; Brown, Natasha J.; Stark, Zornitza; Bruno, Damien L.; Oertel, Ralph; Chong, Belinda; Calabro, Vanessa; Kornberg, Andrew; Sanderson, Christine; Kelly, Julian; Howell, Katherine B.; Savarirayan, Ravi; et al.
Abstract A recurrent proximal microdeletion at 15q25.2 with an approximate 1.5 megabase smallest region of overlap has recently been reported in seven patients and is proposed to be associated with congenital diaphragmatic hernia (CDH), mild to moderate cognitive deficit, and/or features consistent with Diamond–Blackfan anemia. We report on four further patients and define the core phenotypic features of individuals with this microdeletion to include mild to moderate developmental delay or intellectual disability, postnatal short stature, anemia, and cryptorchidism in males. CDH and structural organ malformations appear to be less frequent associations, as is venous thrombosis. There is no consistent facial dysmorphism. Features novel to our patient group include dextrocardia, obstructive sleep apnea, and cleft lip. © 2013 Wiley Periodicals, Inc.